STUDI EKSPERIMENTAL PENGARUH PENAMBAHAN ABU SEKAM PADI NANO DAN BAHAN TAMBAH SUPERPLASTICIZER TERHADAP KUAT TEKAN BETON - Putri Ardiyati; Mira Budi Octaviani; Purwanto Purwanto; Parang Sabdono (Jurnal Karya Teknik Sipil, 2013)
This research aimed to investigate effect of using nano materials rice husk ash and superplasticizer admixture to concrete compressive strength. Nano rice husk ash used as subtitute of pozzolan portland cement. Production of nano rice husk ash use Planetary Ball Milling with  duration of  milling  for 1 hour. To determine effect of using nano materials rice husk ash dan superplasticizer admixture used variation percentage of materials nano rice husk ash such ash 5%, 10%, and 15% with or without superplasticizer admixture. Tests were conducted  at 28 days with uniaxial loading (one-way). Result of this research indicate normal concrete without substitution of nano rice husk ash and without superplasticizer have highest of concrete compressive strength. Concrete with rice husk ash decreased in compressive strength because of rice husk ash absorb much water and increase the length of  hydration process of cement in concrete mix. Although there is a decrease through this research is expected, nano techonology in civil engineering can more developed.